How different is the composition of the fouling layer of wastewater reuse and seawater desalination RO membranes? - Khan, M.; Busch, M.; Molina, V.; Emwas, A.; Aubry, C.; Croue, Jean-Philippe (Elsevier Ltd, 2014)
To study the effect of water quality and operating parameters on membrane fouling, a comparative analysis of wastewater (WW) and seawater (SW) fouled reverse osmosis (RO) membranes was conducted. Membranes were harvested from SWRO and WWRO pilot plants located in Vilaseca (East Spain), both using ultrafiltration as pretreatment. The SWRO unit was fed with Mediterranean seawater and the WWRO unit was operated using secondary effluent collected from the municipal wastewater treatment plant. Lead and terminal SWRO and WWRO modules were autopsied after five months and three months of operation, respectively. Ultrastructural, chemical, and microbiological analyses of the fouling layers were performed. Results showed that the WWRO train had mainly bio/organic fouling at the lead position element and inorganic fouling at terminal position element, whereas SWRO train had bio/organic fouling at both end position elements. In the case of WWRO membranes, Betaproteobacteria was the major colonizing species; while Ca, S, and P were the major present inorganic elements. The microbial population of SWRO membranes was mainly represented by Alpha and Gammaproteobacteria. Ca, Fe, and S were the main identified inorganic elements of the fouling layer of SWRO membranes. These results confirmed that the RO fouling layer composition is strongly impacted by the source water quality. © 2014 Elsevier Ltd.